Wireless power transmission technologies - Alieksieiev, V.O.; Gretskih, D.V.; Gavva, D.S.; Lykhograi, V.G. (Radiotekhnika, 2022)
The article consists of three parts. The analysis of existing technologies of wireless power transfer (WPT) is carried out in the first part. It is noted that one of the factors that determines the choice of one or another WPT technology is the distance over which the power is transmitted and the type of electromagnetic (EM) energy used. The essence of WPT technologies in the near zone, Fresnel zone and Fraunhofer zone is explained. A generalized block diagram of the WPT system is presented. Areas of application and trends in the further development of the WPT technologies over short distances using induction and resonance methods, the WPT technologies over long distances, the technology of EM energy harvesting from the surrounding space and its conversion into direct current for powering low-power devices are considered. The achievements of the team of the antenna laboratory of the Kharkiv National University of Radio Electronics (KhNURE) in the area of WPT are presented in the second part of the article. Namely, the electrodynamics’ approach is considered which is based on a single idea about the functioning of WPT systems and which include antennas and their circuits and ways of excitation with nonlinear elements. The stages of building a nonlinear mathematical model (MM) of the electrodynamics’ level of the WPT system are presented, according to which the entire WPT system, which generally includes the transmitting subsystem and the receiving subsystem, is considered as a single multi-input antenna system with nonlinear characteristics. The proposed MM provides a complete representation of the WPT systems operation of a wide class and purpose, in which fundamentally different WPT technologies are used. The third part of the article presents new results related to continued research. The analysis of the adequacy of the developed MM of WPT system is carried out. The results of simulation of WPT systems with the induction method of energy transfer (near zone) and their comparison with theoretical and experimental data of other authors showed the reliability and universality of the proposed approach and the MM of WPT system developed on its basis.